Factors that Determine the Self-Efficacy of The Maternal Care in Postpartum Women: Data for Future Memory - Sim-Sim, Margarida; Öcal, Hacer Sonmezer; Ayhan, Fatma; Barros, Maria; Aslan, Tuba Korkmaz; Frias, Ana; Zangão, Maria Otília (British Journal of Healthcare and Medical Research, 2023)
The birth of a child demands the provision of care. Mothers have different levels of safety or confidence when it comes to caring, which reveals the perception of self-efficacy. Our aim is to register, for future memory, the factors associated with self-efficacy in maternal care. Quantitative and cross-sectional study. It explores sociodemographic factors, factors related to the pregnancy and labor history, the newborn's characteristics, and related care environment with self-efficacy in maternal care. The study population included postpartum women from two Turkish maternity hospitals, in convenient sampling, with a response rate of 93,4%. Prudent ethical principles. The criterion variable was observed through the Perceived Maternal Parenting Self-Efficacy (PMP S-E). The statistical analysis was carried out on the SPSS software. The participants had an average age of 27.81(DP=5.13), the majority were married (95.9%) and for 40.1% this was their first child. The majority of labors were vaginal (52.4%). When it comes to the criterion variable, about 70% had a high perception regarding self-efficacy in maternal care. The univariate analysis revealed eight variables, included in the logistic regression: maternal age (p=.050), number of children (p<.001), number of prenatal appointments (p=.006), time that elapsed between the birth and the first episode of breastfeeding (p=.047), maternal safety while breastfeeding (p<.001), type of food given to the newborn p=.011), midwife support for exclusive maternal breastfeeding (p<.001) and maternal breastfeeding self-efficacy (p<.001). In the binary logistic regression, the best predictors of self-efficacy in maternal care were: midwife support for exclusive maternal breastfeeding (OR=1.092; B=0,088) and the self-efficacy in the maternal breastfeeding (OR=13.187; B=2.579). When it comes to maternal breastfeeding, both from the perspective of self-efficacy and the support offered by professionals, are the most relevant factors in the perception of maternal skills recognized by mothers. This study fills an information gap about the phenomenon, looking at it in retrospect.